How A Prosvektif Maths Teacher Builds Their Teacher Self-Efficacy - Nisra, Nisraeni; Riyadi, Riyadi; Triana, Dinny Devi (IJBLE Scientific Publications Community Inc., 2024)
Self-efficacy is commonly conceptualised as being contingent upon a particular domain of endeavour. The appropriate understanding of self-efficacy relies heavily on the precise specification of its scope. When the scope of the domain is either excessively broad or excessively narrow, the accuracy of self-efficacy diminishes or it may lose its importance. Furthermore, the concept of a domain inherently requires the existence of sophisticated regulatory mechanisms, so rendering the mastery of rudimentary and repetitive tasks, such as the process of tying shoelaces, devoid of significance. Three interrelated domains were discovered, namely efficacy for classroom management, efficacy for student engagement, and efficacy for instructional methodologies